The effects of embedded dipoles in aromatic self-assembled monolayers - Abu Husein, Tarek Naser; Schuster, Swen; Egger, David A.; Kind, Martin; Santowski, Tobias; Wiesner, Adrian; Chiechi, Ryan; Zojer, Egbert; Terfort, Andreas; Zharnikov, Michael (Advanced functional materials, 2015)
Using a representative model system, here electronic and structural properties of aromatic self-assembled monolayers (SAMs) are described that contain an embedded, dipolar group. As polar unit, pyrimidine is used, with its orientation in the molecular backbone and, consequently, the direction of the embedded dipole moment being varied. The electronic and structural properties of these embedded-dipole SAMs are thoroughly analyzed using a number of complementary characterization techniques combined with quantum-mechanical modeling. It is shown that such mid-chain-substituted monolayers are highly interesting from both fundamental and application viewpoints, as the dipolar groups are found to induce a potential discontinuity inside the monolayer, electrostatically shifting the core-level energies in the regions above and below the dipoles relative to one another. These SAMs also allow for tuning the substrate work function in a controlled manner independent of the docking chemistry and, most importantly, without modifying the SAM-ambient interface.
Gesehen am 22.09.2020